The miR-1269a/PCDHGA9/CXCR4/β-catenin pathway promotes colorectal cancer invasion and metastasis - Haitao Mei; Qingshan Luo; Junyong Weng; Jialing Hao; Jinfeng Cai; Runkai Zhou; Ce Bian; Yingzi Ye; Shengzheng Luo; Yugang Wen (Cellular & Molecular Biology Letters)
Abstract Background Colorectal cancer (CRC) is the third most common cancer worldwide and the second leading cause of cancer-related death. This research focuses on investigating the impact and underlying molecular mechanisms of protocadherin gamma subfamily A, 9 (PCDHGA9) on the invasion and metastasis of CRC, aiming to identify more precise molecular markers for the diagnosis and prognosis of CRC. Methods PCDHGA9 expression was detected using quantitative real-time quantitative polymerase chain reaction (RT-qPCR) in 63 pairs of colorectal cancer tissues. Differential gene expression from high-throughput sequencing was analyzed using ingenuity pathway analysis (IPA) to explore the biological functions of PCDHGA9 and its potential regulated genes. Bioinformatics tools were employed to explore potential upstream regulatory microRNAs of PCDHGA9. Dual-luciferase assays were performed to demonstrate the regulation between PCDHGA9 and miR-1269a. Protein mass spectrometry suggested an interaction between PCDHGA9 and HOXA1. JASPAR predicted that HOXA1 may act as a transcription factor of CXCR4. Coimmunoprecipitation, dual-luciferase assays, and nuclear–cytoplasmic fractionation experiments confirmed the molecular mechanism involving PCDHGA9, CXCR4, HOXA1, and β-catenin. Transwell, wound healing, and western blot assays were conducted to confirm the impact of PCDHGA9, miR-1269a, and CXCR4 on the invasion, metastasis, and epithelial–mesenchymal transition (EMT) functions of CRC cells in in vitro experiments. A whole-body fluorescence imaging system was used to evaluate the combined impact of miR-1269a and PCDHGA9 on the invasion and metastasis of CRC in in vivo experiments. Results The expression of PCDHGA9 was found to be lower in CRC tissues compared with their corresponding adjacent tissues. Low expression of PCDHGA9 potentially correlated with worse prognosis and increased chances of invasion and metastasis in CRC. miR-1269a was highly expressed in CRC tissues and acted as a negative regulator for PCDHGA9, promoting invasion, migration, and EMT of CRC cells. PCDHGA9’s interaction with HOXA1 downregulated CXCR4, a transcription factor, leading to accumulation of β-catenin and further promoting invasion, migration, and EMT of CRC cells. Conclusions PCDHGA9, acting as a tumor suppressor, is downregulated by miR-1269a. The low level of PCDHGA9 activates the Wnt/β-catenin pathway by releasing its interaction with HOXA1, promoting the expression of CXCR4, and causing invasion, migration, and EMT in CRC. Graphical Abstract